Effectiveness Evaluation of Alternative Technologies Applied in Centralized Domestic Wastewater Treatment Systems - Ahmad Mubarok; Widya Ernayati; Sjaifuddin Sjaifuddin (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
The paper aims to determine the effectiveness of several alternative technologies that have been applied in centralized domestic wastewater management systems, especially in West Java and Banten provinces, in the removal of domestic wastewater pollutant parameters. The study was conducted in SPALD-Ts, including the Anaerobic Baffle Reactor (ABR) system, the Anobic Filter (AF) system, the combined ABR + AF system, and the Extended Aeration. The analysis was performed by sampling at the inlet and outlet points of the system for three consecutive years with sampling times from 2021 - 2023. The results of the research show that the efficiency of pollutant parameter separation based on the best technology in the separation of domestic wastewater pollutant parameters is the SPALDT extended aeration technology, where this technology can separate pollutant parameters up to an average of 88.25%, but in this technology requires more cost and periodic maintenance.